Implementation of an ISO 45001-Based Occupational Health and Safety Management System in Healthcare Companies - Sari, Siti Nurmanis; Deviyanti, Andi Yepita; Hardianty, Hardianty (Oshada, 2025)
The implementation of an ISO 45001-based Occupational Safety and Health (OHS) Management System in healthcare companies is a strategic effort to improve workforce safety and the quality of healthcare services sustainably. This study uses a qualitative method with a literature review approach to examine the effectiveness, obstacles, and strategies for strengthening the implementation of ISO 45001. The analysis results indicate that the implementation of this standard can reduce the rate of workplace accidents, increase compliance with safety procedures, and strengthen an organizational culture oriented towards risk prevention. However, obstacles such as limited human resource competency, work culture resistance, and financial constraints remain significant challenges. Effective strengthening strategies include transformative leadership, continuous training, quality management system integration, and the use of digital technology to strengthen audits and reporting. The implementation of ISO 45001 has been proven not only to improve operational efficiency but also to build public trust in the professionalism of healthcare organizations. In conclusion, the successful implementation of an ISO 45001-based OHS management system is determined by the synergy between managerial commitment, structural readiness, and a sustainable safety culture, which together serve as an important foundation for improving the quality and sustainability of healthcare services.